2012 Second International Conference on Digital Information Processing and Communications (ICDIPC) 2012
DOI: 10.1109/icdipc.2012.6257297
|View full text |Cite
|
Sign up to set email alerts
|

e-Learning, Web 2.0 and beyond

Abstract: Integration of Web based ICT tools in education aiming to bring quality education to everyone and everywhere is a worldwide phenomenon. Teachers and learners are benefited as these tools increase efficiency and effectiveness of learning, teaching, planning and managing by establishing linkages and collaboration, facilitating experimentation and lifelong learning and providing easy to use management and administrative tools. Web has created various opportunities for extending teacher-learner, learner-learner an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0
6

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 28 publications
0
1
0
6
Order By: Relevance
“…Using this technology in e-learning make students to be active in creating, collaborating, editing, and sharing their learning contents, and it facilitates discussion for students in interactive manner under the supervision of teachers [14]. While Ulf Daniel Ehlers's researched concluded that e-learning 2.0 is using social software and learning services that can be combined according to individual needs.…”
Section: B E-learning 20mentioning
confidence: 99%
“…Using this technology in e-learning make students to be active in creating, collaborating, editing, and sharing their learning contents, and it facilitates discussion for students in interactive manner under the supervision of teachers [14]. While Ulf Daniel Ehlers's researched concluded that e-learning 2.0 is using social software and learning services that can be combined according to individual needs.…”
Section: B E-learning 20mentioning
confidence: 99%
“…Nesse contexto, atividades colaborativas e interações sociais configuram importantes incrementos funcionais para os AEUs [Banday 2012, Chiu et al 2009]. Por meio desses sistemas, o conteúdo apresentado pode ser estendido, refinado e enriquecido, além de incentivar o compartilhamento de informações, a troca de experiências e o debate entre os usuários.…”
Section: Congresso Brasileiro De Informática Na Educação (Cbie 20unclassified
“…As tecnologias que hoje são disponibilizadas propiciam a maximização da aprendizagem colaborativa e a ruptura de conceitos pedagógicos antigos. Tais ferramentas mudam o paradigma tradicional de ensino, no qual o professoŕ e aúnica entidade a prover conteúdo educacional, emergindo para um cenário no qual os estudantes têm papel ativo e influente nos processos cognitivos dos membros da comunidade a qual estão inseridos [Banday 2012]. Na realidade, hoje nosé apresentado um cenário tecnológico que permite o amplo acesso a informação a qualquer hora e em qualquer lugar, o que propicia aos estudantes incentivosà promoção do conhecimento e responsabilidade quanto a seu próprio processo de aprendizagem.…”
Section: Conclusõesunclassified
“…Tais interações, além de promover o enriquecimento contínuo do conteúdo educacional por meio da inclusão das impressões e anotações dos usuários, propiciam a geração de metainformação que pode ser utilizada como parâmetro para recomendação e personalização de conteúdo. Por meio de atividades colaborativas e interação social entre os usuários dos AEUs, conteúdos educacionais podem ser estendidos, renados e enriquecidos, tornando-se poderosas fontes de apoio ao ensino e à aprendizagem (Banday, 2012;Nokelainen et al, 2003;Tseng et al, 2010).…”
Section: Motivaçãounclassified
“…Aplicações que exploram o paradigma da Web 2.0 são fortes candidatas a prover mecanismos de interação, troca de informações, extensão e classicação de conteúdo dentro dos AEUs (Chiu et al, 2009;Wan, 2010). Tais ferramentas mudam o paradigma tradicional de ensino, no qual o professor é a única entidade a prover conteúdo, emergindo para um cenário no qual os estudantes têm papel ativo e inuente nos processos cognitivos dos membros das comunidades virtuais às quais estão inseridos (Banday, 2012).…”
Section: Atividades Sociais E Colaborativas Em Ambientes Educacionais Ubíquosunclassified